How should we test infant handedness?. Issue 3 (4th May 2017) - Fagard, Jacqueline; Margules, Sylvie; Lopez, Clémence; Granjon, Lionel; Huet, Viviane
ABSTRACT: As soon as infants grasp objects, they exhibit some degree of hand preference. Although all studies agree that the number of non-lateralized infants remains high during the first months of life, there is no consensus on the percentage of right- and left-handed infants. Reasons might be the different formulae used to calculate an handedness index, the basis on which handedness categories are distinguished, and the number of trials per session. In this study we aimed to provide a valid method of testing handedness, reliable without being lengthy so as to combine it with other evaluations. We tested 46 infants at 9 and 11 months by giving them 34 trials. We compared the results using 2 of the most used formulae, including the bimanual grasps or not, and considering the first 5, 10, 15, 20, 26, 31, or all 34 trials. The results show that different formulae do not give significantly different results as long as bimanual grasps are included. The number of trials is important: 15 trials are necessary for the reliability of the classification into handedness categories. Giving more trials does not provide substantial additional information.